2017
DOI: 10.1111/birt.12327
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to birth without epidural in a tertiary obstetric referral center: Perspectives of health care professionals and patients

Abstract: Reconciling patient birth goals with staff focus on patient safety is challenging in the tertiary context. Discrepancies between health care professional and patient attitudes about childbirth pain may influence decision-making about epidural use. Maintaining labor support skills is challenging for health care professionals who have limited exposure to birth without epidural. There is a need to allocate dedicated resources to better support birth without epidural. Specifically, support could be improved throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Providing pain relief using effective analgesia like epidural is very important, considering that the process of childbirth is a life-changing event and the care which a pregnant woman receives during this important event may have a long-term emotional and psychological impact on her and this by extension may affect the health of the baby (16). This is consistent with the finding by Lim et al who reported that the extent of labor pain relief by epidural analgesia predicts lower postpartum depression scores (17). A parturient in labor should have a satisfying birthing experience that would make her look forward to her next pregnancy with enthusiasm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Providing pain relief using effective analgesia like epidural is very important, considering that the process of childbirth is a life-changing event and the care which a pregnant woman receives during this important event may have a long-term emotional and psychological impact on her and this by extension may affect the health of the baby (16). This is consistent with the finding by Lim et al who reported that the extent of labor pain relief by epidural analgesia predicts lower postpartum depression scores (17). A parturient in labor should have a satisfying birthing experience that would make her look forward to her next pregnancy with enthusiasm.…”
Section: Discussionsupporting
confidence: 91%
“…Similar studies have also adduced comparable reason for poor utilization in some other similar settings (8,13). Knox et al identified several contextual factors which facilitated or were barriers to birth without epidural analgesia in tertiary health centers in Canada, with the following themes emerging from differing perceptions of pain, care providers ready for things to go wrong and insufficient resources (17).…”
Section: Discussionmentioning
confidence: 76%
“…In labor and delivery, alleviating anxiety and stress in both mother and her companion is important to achieve an optimum outcome for both mother and baby. 7,5,17,18 In contrast to birthing, in end-of-life care, pain suppression is often prioritized over the need to alleviate anxiety and stress. 4,16,22 However, through similar practices used during childbirth, nurses in hospice care can help create a state of well-being in their patients diminishing their level of anxiety 19 and contributing to pain control.…”
Section: Anxiety and Stress Reductionmentioning
confidence: 99%
“…[5][6][7]18,20 Prenatal education is critical in enabling mothers to make informed choices. 7 When a woman feels in control and participates in the decision-making process, it increases her satisfaction with the childbirth experience. This leads to fewer medical interventions and improves outcomes for both mother and newborn.…”
Section: Self-care and Empowermentmentioning
confidence: 99%
See 1 more Smart Citation